Efficacies of S-nitrosoglutathione (GSNO) and GSNO reductase inhibitor in SARS-CoV-2 spike protein induced acute lung disease in mice - Kim, Judong; Qiao, Fei; Singh, Avtar K.; Won, Jeseong; Singh, Inderjit (Frontiers in Pharmacology, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which initially surfaced in late 2019, often triggers severe pulmonary complications, encompassing various disease mechanisms such as intense lung inflammation, vascular dysfunction, and pulmonary embolism. Currently, however, there's no drug addressing all these mechanisms simultaneously. This study explored the multitargeting potential of S-nitrosoglutathione (GSNO) and N6022, an inhibitor of GSNO reductase (GSNOR) on markers of inflammatory, vascular, and thrombotic diseases related to COVID-19induced acute lung disease. For this, acute lung disease was induced in C57BL/6 mice through intranasal administration of recombinant SARS-CoV-2 spike protein S1 domain (SP-S1). The mice exhibited fever, body weight loss, and increased blood levels and lung expression of proinflammatory cytokines (e.g., TNF-α and IL-6) as well as increased vascular inflammation mediated by ICAM-1 and VCAM-1 and lung infiltration by immune cells (e.g., neutrophils, monocytes, and activated cytotoxic and helper T cells). Further, the mice exhibited increased lung hyperpermeability (lung Evans blue extravasation) leading to lung edema development as well as elevated blood coagulation factors (e.g., fibrinogen, thrombin, activated platelets, and von Willebrand factor) and lung fibrin deposition. Similar to the patients with COVID-19, male mice showed more severe disease than female mice, along with higher GSNOR expression in the lungs. Optimization of GSNO by treatment with exogenous GSNO or inhibition of GSNOR by N6022 (or GSNO knockout) protects against SP-S1-induced lung diseases in both genders. These findings provide evidence for the potential efficacies of GSNO and GSNOR inhibitors in addressing the multi-mechanistic nature of SARS-CoV-2 SP-associated acute-ling disease.